LAYANAN PEMBELAJARAN BERBASIS E-LEARNING - Rusman, Rusman (MAJALAH ILMIAH PEMBELAJARAN, 2009)
E-learning is a general term used to refer to computer-enhanced learning based that facilitates whoever, wherever, and whenever the person is to be able to learn more fun, easier and cheaper by using Internet. In other words, E-learning is the use of network technologies to create, foster, deliver, and facilitate learning, anytime and anywhere. It also means a learning facility that uses electronic devices such as LAN, WAN, or Internet to give lectures, to interact, or to guide and monitor the students. E-learning is naturally suited to distance learning and flexible learning. This learning is an asynchronous or self-directed; self-paced activity that is used in order for the students to obtain learning materials by using electronic computer devices that are designed to help the students to get learning materials needed. Asynchronous consists of learning that is stand-alone. Asynchronous eLearning can be delivered through the web, via an Intranet, or by way of an extranet. The Curriculum and Education Technology Department of Indonesia University of Education is now trying to design and to use this E-learning as a supplement in MKDP curriculum and learning subjects. The department has been trying to develop the research on E-learning by using research method and development. The instrument used comprises questionnaires meanwhile the data analysis used are descriptive data analysis. Based on the result of the research, it shows that e-learning program is able to assist the lecturers of MKDP curriculum and learning subjects to improve their ability in designing and developing learning design based on electronic devices by using models and program software.